Pathogenicity evaluation of low pathogenic Avian Influenza (H9N2) virus isolated from layer flocks in Malaysia in specific-pathogen-free chickens - Gunasekara, Erandi Maheshika; Raji, Abdullahi Abdullahi; Mahamud, Siti Nor Azizah; Bejo, Mohd Hair; Ideris, Aini; Omar, Abdul Rahman (Universiti Putra Malaysia, 2024)
Infection with the low pathogenic avian influenza (LPAI) H9N2 virus has been reported worldwide and poses a health risk to poultry as well as to global health due to its ability to re-assort with other avian influenza viruses. Besides, the silent spread of the H9N2 infection causes significant economic damage to the poultry industry. Recently, Malaysia reported major outbreaks of LPAI H9N2 in commercial layer chicken flocks. Genome sequence analysis indicated that the predominant LPAI H9N2 viruses are of the Y280/ BJ94-like lineages. However, the pathogenicity of the virus has not been evaluated. This study determines the pathogenicity of LPAI H9N2 strain UPM994/2018, previously isolated from commercial layer chickens, in one-week-old specific-pathogen-free (SPF) chickens. Clinical signs such as ruffled feathers, mild tracheal rales, facial edema, sero-nasal discharge, and diarrhea were observed from days 6 to 10 post-inoculation (PI). However, no mortality was recorded. Based on a real-time polymerase chain reaction assay, the viruses can be detected in the lungs, trachea, and kidneys of the inoculated chickens on the second day, increased until day 10, then declined at day 16 PI. However, swab samples collected from the oropharyngeal and cloacal regions remain positive from day 2 to day 14 PI, with the highest viral load detected at day 10 PI. In conclusion, although the virus is an LPAI, it is pathogenic in SPF chickens, causing respiratory, gastrointestinal, and renal-associated illnesses.